Rehabilitation Management of Intensive Care Unit-acquired Weakness (ICU-AW): A Narrative Review - Nazir, Arnengsih; Anggraini, Gabriela (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Intensive Care Unit-acquired weakness (ICU-AW) is one of the most common neuromuscular disorders affecting intensive care unit (ICU) patients' outcomes and clinical course. ICU-AW is found in 30-50% of patients and increases to 67% in sepsis-critically ill patients. Prolonged ICU stay, the difficulty of weaning from the ventilator, higher hospitalization costs, and an increase in mortality, as well as long-term morbidity, are associated with ICU-AW. ICU-AW causes skeletal muscle weakness, including respiratory muscles, which results in complications that continue even years after being discharged from the hospital. Aim: To describe the rehabilitation management of ICU-AW and provide the information needed clinically to manage these patients. Methods: The authors reviewed all types of articles without time filtering using PubMed and Google Scholar databases with